Outside Front Cover: Volume 3 Issue 4. Issue 4 (20th December 2022) - Zhang, Zhixing; Yu, Yunfei; Yu, Huitao; Feng, Yiyu; Feng, Wei
Abstract : Outside front cover image : A customizable and multi‐functional electronic conductive organogel is proposed by combining conductive carbon nanotube clusters and flexible adhesive organogels. Based on customizable conductive networks and entropy‐driven organogel actuation, the conductive organogels can sense various strain and stress signals and imitate natural organisms with muscle actuation and neurofeedback. This strategy for preparing electronic conductors can enhance the rational design of soft robotics and flexible sensors, facilitating further progress of artificial intelligent systems. (DOI: https://doi.org/10.1002/smm2.1108 )